2020
DOI: 10.3389/fnins.2019.01406
|View full text |Cite
|
Sign up to set email alerts
|

Altered Default Mode Network Dynamics in Civil Aviation Pilots

Abstract: Background: Airlines occupy an increasingly important place in the economy of many countries. Because air disasters may cause substantial losses, comprehensive surveys of the psychophysiological mechanism of flying are needed; however, relatively few studies have focused on pilots. The default mode network (DMN) is an important intrinsic connectivity network involved in a range of functions related to flying. This study aimed to examine functional properties of the DMN in pilots. Method: Resting-state function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…[ 22 ] Notably, as the 2 main components of the FPN, the dorsolateral prefrontal cortex and precuneus are both relatively more sensitive to hypoxia. [ 6 , 7 , 16 ] Moreover, the FPN, which comprises the frontal eye fields and the lateral intraparietal area, has a pivotal role in complex cognitive control of higher-order brain functions, including oculomotor control, motor preparation, visual attention, and decision-making. [ 23 ] In this study, we found that the inter-network connectivities between the FPN and VN were reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 22 ] Notably, as the 2 main components of the FPN, the dorsolateral prefrontal cortex and precuneus are both relatively more sensitive to hypoxia. [ 6 , 7 , 16 ] Moreover, the FPN, which comprises the frontal eye fields and the lateral intraparietal area, has a pivotal role in complex cognitive control of higher-order brain functions, including oculomotor control, motor preparation, visual attention, and decision-making. [ 23 ] In this study, we found that the inter-network connectivities between the FPN and VN were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The brain network functional connectivity model at rest reflects the significant coupling of spontaneous fluctuations in ongoing activities and provides a neuroanatomical basis for understanding human behavior and cognitive function. [ 6 ] Recently, resting-state functional magnetic resonance imaging (fMRI), which is based on the blood oxygen level dependent signal’s ability to indirectly reflect the activity of neurons in the brain, [ 7 ] has been used to explore the effect of hypoxia on cognitive function. [ 8 10 ] To investigate the cognitive and brain functional alterations associated with exposure to high-altitude hypoxia, Chen et al used resting-state fMRI to quantify brain functional connectivity alterations and found that differences in functional connectivity before and after hypoxia exposure in multiple brain regions were significantly correlated with cognitive changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were fully informed about the procedure, and we obtained written informed consent. Detailed information of the participants can be found in our previous study [13].…”
Section: Participantsmentioning
confidence: 99%
“…The core regions of the DMN are the medial prefrontal cortex, the precuneus/posterior cingulate cortex, and the bilateral parietal cortex [12]. Pilots have been found to exhibit increased functional connections within the DMN [13]. The DMN is always deactivated during stimulus-activation cognitive tasks and activated during the resting state [14].…”
Section: Introductionmentioning
confidence: 99%